Experimental analysis of reinforced concrete columns strengthened with Self-Compacting concrete - Omar,M. Y. M. (2010)
This paper presents the results of reinforced concrete columns strengthened by addition of a self-compacting concrete overlay at the compressed and at the tensioned face of the member, with and without addition of longitudinal steel bars. Eight columns were submit- ted to loading with an initial eccentricity of 60 mm . These columns had 120 mm x 250 mm of rectangular cross section, 2000 mm in length and four longitudinal reinforcement steel bars with 10 mm in diameter. Reference columns P1 and P2 were tested to failure without any type of rehabilitation. Columns P3 to P8 were loaded to a predefined load (close to the initial yield point of tension reinforce- ment), then unloaded and strengthened for a subsequent test until failure. Results showed that the method of rehabilitation used was effective, increasing the loading capacity of the strengthened pieces by 2 to 5 times the ultimate load of the reference column.